KEDUDUKAN OERASI TANGKAP TANGAN (OTT) PEGAWAI NEGERI SIPIL (PNS) DALAM TINDAK PIDANA KORUPSI - Immanuel Simanjuntak Simanjuntak (jurnal.unprimdn.ac.id, 2019)
Operation Catching Hands is indeed not intended as a legal term let alone implementing a norm, but a name of the type of operation carried out by the Corruption Eradication Commission, the Police or others based on Article 18 of the Criminal Procedure Code. Article 18 of the Criminal Procedure Code is an example of a norm, which basically stipulates that those authorized to carry out arrests are carried out by police officers and must be accompanied by an arrest warrant. So that civil servants who are convicted of corruption cases are terminated disrespectfully according to article 87 paragraph (4) letter b of Law Number 5 of 2014 concerning State Civil Apparatus.